(untitled) - Jurkovic, Martin; Sosedova, Jarmila; Filova, Eva (Doprava a spoje, 2011)
The potential uses of Vah river route as an alternative to the highway network, relocating some of its transport currents to the waterway, as a recreational, sport and water-resources area will be very significant after its completion. Even though the priorities in transport infrastructure in Slovakia are towards the road transport (especially highway) network, it is essential to start up the processes of development alternative carriage infrastructure.